2015
DOI: 10.1002/anie.201506267
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically Shifting Nitroxides for EPR Spectroscopy and Overhauser‐Enhanced Magnetic Resonance Imaging

Abstract: In vivo investigations of enzymatic processes using non-invasive approaches are a long-lasting challenge. Recently, we showed that Overhauser-enhanced MRI is suitable to such a purpose. A β-phosphorylated nitroxide substrate prototype exhibiting keto-enol equilibrium upon enzymatic activity has been prepared. Upon enzymatic hydrolysis, a large variation of the phosphorus hyperfine coupling constant (Δa(P)=4 G) was observed. The enzymatic activities of several enzymes were conveniently monitored by electronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…Free radicals such as nitroxides or trityl radicalsa re stable enough in physiological conditions (in vitro and in vivo) to be detected by electronic paramagnetic resonance( EPR). [16] Preliminary investigationsi no ur groups [17][18][19] indicated that nonradicale nzymatic activity can be investigated both by EPR and OMRI using signal changes based either on the linewidthb roadening effect [17,18] or on the shift [19] of hyperfine coupling constant of an itroxide. Unfortunately,d ue to the very fast relaxation of free electron, EPR imaging( EPRI) is at the moments low and insufficiently resolved.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Free radicals such as nitroxides or trityl radicalsa re stable enough in physiological conditions (in vitro and in vivo) to be detected by electronic paramagnetic resonance( EPR). [16] Preliminary investigationsi no ur groups [17][18][19] indicated that nonradicale nzymatic activity can be investigated both by EPR and OMRI using signal changes based either on the linewidthb roadening effect [17,18] or on the shift [19] of hyperfine coupling constant of an itroxide. Unfortunately,d ue to the very fast relaxation of free electron, EPR imaging( EPRI) is at the moments low and insufficiently resolved.…”
mentioning
confidence: 99%
“…Consequently,t he reactionw as repeated under different conditions (e.g.,M g(ClO 4 ) 2 ,1 00 8C, ammonium acetate which also failed to improve the yield of the reaction. [19] Enantiomers of 1C were separated by using aC hiralpak-IEc olumn (1aC, t R = 6.21 min, 1bC, t R = 7.64 min in 1:1h eptane/ethanol at 1mLmin À1 flow rate). Finally,1 0mol %o fF eCl 3 was found to be an efficient catalyst for this reaction providing the amino-phosphonate 3 in 87 %y ield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work demonstrated the detection of proteases using a β-phosphorylated NR-substrate prototype [11] and an NR-labeled peptide specific to chymotrypsin and cathepsin G. [12] Upon enzymatic hydrolysis of the peptide, the enol ester moiety of the NR is converted into a ketone moiety accompanied by a large 4 to 5 G change of the phosphorus hyperfine splitting (hfs) constant. Note that the measurement of hfs changes provides higher specificity than changes in correlation time or spin exchange, as the latter are sensitive to the local environment.…”
mentioning
confidence: 99%
“…[11] One can expect a significant change in the nitrogen hfs upon the change in ring conformation, therefore allowing for discrimination between NRs 1 and 2 that exhibit narrow EPR linewidths due to deuteration.…”
mentioning
confidence: 99%